Genetic Diagnosis of Oculocutaneous Albinism Type 1A: A Novel TYR Variant - Raghad N. Shihab; Rusul Thabit Hamid; Mostafa Neissi; Javad Mohammadi‐Asl; Motahareh Sheikh‐Hosseini; Elaheh Nekouei (Clinical Case Reports)
ABSTRACT Oculocutaneous albinism type IA (OCA1A) is a rare autosomal recessive disorder caused by variants in the TYR gene, resulting in complete loss of tyrosinase activity and absence of melanin production. In this study, we report a novel missense variant, TYR (NM_000372.5):c.143A>C (p.Gln48Pro), found within exon 1 and mapped to chr11: g.89178096A>C (GRCh38/hg38). This variant was identified through exome sequencing in a 4‐year‐old Iranian girl from a consanguineous family presenting with features of OCA1A. This discovery expands the mutational spectrum of OCA1 and underscores the importance of genetic screening in diagnosing rare inherited disorders. Future studies involving functional assays are necessary to elucidate the molecular mechanisms of this variant and its potential impact on melanogenesis.